HOW TO MAKE AN ENTREPRENEURIAL STATE: WHY INNOVATION NEEDS BUREAUCRACY (Farabi Journal of Social Sciences, 2024)
“How to Make an Entrepreneurial State: Why Innovation Needs Bureaucracy” by Rainer Kattel, Wolfgang Drechsler, and Erkki Karo offers an analytical approach to creating successful “innovation bureaucracies” with a wealth of exemplary policies, practices, and institutions observed throughout the post-Second World War era. The book defines the quality of “agile stability” that the public sector needs to create in order to solve next-generation problems. As its title speaks, its main argument is: “Innovation needs bureaucracy.” Therefore, the authors give a detailed account of how public institutions create, do (perform), fund, intermediate, and rule (administer/coordinate). The book gives a detailed account of these typologies of innovation institutions, from the US’s DARPA to Sweden’s Vinnova. It is a reference source for students, scientists, practitioners, and anyone who cares about innovating successfully and developing prosperous societies while facing tomorrow’s challenges.Keywords: agile stability, innovation bureaucracies, neo-Weberian innovation agencies. Information about the author:Halil Deligöz - PhD in International Relations. Independent Scholar, (Ankara, Turkiye, e-mail: halimdeligoz@gmail.com)